Pam Allen letter to Jim Fuller regarding Greater Scaup addendum for the Fall report, June 3, 1994 - Allen, Pamet al (1994)
Letter from Pam Allen to Jim Fuller dated June 3, 1994. Allen noticed that the Fall report published in Iowa Bird Life did not include her sighting of a Greater Scaup. She also notes from her Spring report that she was really happy to see a Purple Gallinule. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed